Interobserver agreement between senior radiology resident, neuroradiology fellow, and experienced neuroradiologist in the rating of Alberta Stroke Program Early Computed Tomography Score (ASPECTS) - Kobkitsuksakul, Chai (Diagn Interv Radiol, 2018)
PURPOSE: The distribution of ischemic changes caused by infarction of the middle cerebral artery (MCA) territories is usually measured using the Alberta Stroke Program Early Computed Tomography Score (ASPECTS). The first interpreter of the brain computed tomography (CT) in the emergency department is the on-call radiology resident. The primary objective of this study was to describe the agreement of the ASPECTS performed retrospectively by the resident compared with expert raters. The second objective was to ascertain the appropriate window setting for early detection of acute ischemic stroke and good interobserver agreement between the interpreters. METHODS: We identified consecutive patients presenting with hemiparesis or aphasia at the emergency department who underwent brain CT and CT angiography. Each scan was rated using ASPECTS by senior radiology resident, neuroradiology fellow, and later by consensus between two expert raters. Statistical analysis included determination of Cohen’s kappa (κ) coefficient and intraclass correlation coefficient (ICC). RESULTS: A total of 43 patients met our study criteria. Interobserver agreements for ASPECTS varied from 0.486 to 0.678 in Cohen’s κ coefficient between consensus of two neuroradiologists and a neuroradiology fellow, and from 0.198 to 0.491 for consensus between two neuroradiologists and a senior radiology resident. ICC among three raters (expert consensus, neuroradiology fellow, and senior radiology resident), was very good when 8 HU window width and 32 HU center level setting was used. CONCLUSION: ASPECTS varied among raters. However, when using a narrowed window setting for interpretation, interobserver agreement improved.